2017
DOI: 10.3325/cmj.2017.58.395
|View full text |Cite
|
Sign up to set email alerts
|

Anemia, hypoalbuminemia, and elevated troponin levels as risk factors for respiratory failure in patients with severe exacerbations of chronic obstructive pulmonary disease requiring invasive mechanical ventilation

Abstract: AimTo determine in-hospital and post-discharge mortality, readmission rates, and predictors of invasive mechanical ventilation (IMV) in patients treated at intensive care unit (ICU) due to acute exacerbations of chronic obstructive pulmonary disease (AECOPD).MethodsA retrospective observational cohort study included all patients treated at a respiratory ICU for AECOPD during one year. A total of 62 patients (41 men) with mean age 68.4 ± 10.4 years were analyzed for outcomes including in-hospital and post-disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Previous reports have estimated the incidence of anemia (hemoglobin <120 g/L) at 18%‐79.9% in COPD patients requiring IMV . Many studies have shown that anemia affects the prognosis of AECOPD patients, especially when the patient requires mechanical ventilation (IMV or NIV) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous reports have estimated the incidence of anemia (hemoglobin <120 g/L) at 18%‐79.9% in COPD patients requiring IMV . Many studies have shown that anemia affects the prognosis of AECOPD patients, especially when the patient requires mechanical ventilation (IMV or NIV) …”
Section: Discussionmentioning
confidence: 99%
“…14,15 Many studies have shown that anemia affects the prognosis of AECOPD patients, 27 especially when the patient requires mechanical ventilation (IMV or NIV). [13][14][15][16] Causes of anemia in COPD are multifactorial. Anemia may develop in response to chronic disease, inflammation, iron and vitamin deficiencies, comorbidities, or hypogonadism, or anemia may be treatment related.…”
Section: T a B L E 5 Pairwise Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Next to interdependency, decline of both motor and cognitive function may be further enhanced by certain conditions common in the older population, such as COPD and low HB (hemoglobin) level [5][6][7][8]. When individuals suffer from both low HB level and COPD, existing evidence indicates that outcomes such as the development of respiratory failure and mortality in critically ill hospitalized patients but also in the general population may occur more frequently than in persons who suffer only from one condition [9] [10]. Both factors have previously been shown to independently reduce exercise capability and increase feelings of dyspnea [11], while persons suffering from both conditions reported lower quality of life compared to persons with COPD alone [12].…”
Section: Introductionmentioning
confidence: 99%